The emergence of collective intelligence - Gunasekaran S.S.; Mostafa S.A.; Ahmad M.S. (2023)
Intelligence is the logical ability of an entity to pursue its goal and ultimately achieving it successfully. Consequently, by comprehending and applying such ability in a collective environment, optimum results in goal attainment can be achieved. Such evidence is visible through the model of swarm intelligence in which entomological studies have been made to identify the social interactive behavior of ant and bee colonies. Harvesting successful collective behavior among these insects with such low level logical ability instigates further research on capturing the collective behavior of humans, who possess much higher state of intelligence. In this paper, we investigate and identify the emergence of collective intelligence amongst humans. This is done through the observation of face-to-face meetings in which two or more human entities are involved in formal and informal discussions. In this paper, the term personal intelligence is introduced to describe it's influence in generating successful Collective Intelligence. Finally, a preliminary theory is introduced to support the concept of Collective Intelligence. 2013 IEEE.